The Future of Learning is Hybrid: Exploration of EdTech's Role in Shaping the Post-Pandemic Educational Landscape - Sayed Mahbub Hasan Amiri; Prasun Goswami; Md. Mainul Islam; Mohammad Sohel Kabir; Mohammad Shakhawat Hossen (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
The global COVID-19 pandemic acted as a profound catalyst, forcing an unprecedented and rapid shift to remote learning and exposing both the potential and the deep-seated vulnerabilities within global education systems. This paper argues that the post-pandemic educational landscape is irrevocably shifting towards a hybrid learning model, which integrates face-to-face instruction with technology-mediated learning experiences. This transition is not merely a temporary adjustment but a fundamental restructuring of pedagogical delivery, with Educational Technology (EdTech) at its core. The paper explores the dual role of EdTech as both an enabler of flexibility, personalization, and accessibility, and a potential amplifier of existing inequalities the